Electromagnetic Modeling and Dynamic Simulation of Combined Propulsion, Levitation, and Guidance System in EDS - Tan, Yiqiu; Zhou, Danfeng; Xiao, Boqi; Chen, Qiang; Li, Jie (IEEE transactions on applied superconductivity, 2024)
In this article, the decoupling calculation of the active and passive components of the electromagnetic force of the null-flux coil electrodynamic suspension system with combined propulsion, levitation, and guidance (PLG) is carried out, the theoretical electromagnetic modeling of the PLG system is completed, and its electromagnetic performance is analyzed. Then, the accuracy of the theoretical model is verified by the experimental data of the Miyazaki test line in Japan. Based on the precise theoretical model, the cosimulation model of the PLG system is built based on Simulink and dynamic simulation software SIMPACK, so as to analyze the dynamic characteristics of the system under different working conditions. The dynamic cosimulation model in this article lays a foundation for further study of the PLG system.